Photocatalysis of titanium dioxide to decompose pesticide ethion in tangerine fruit - S. Hassarangsee (2018)
The reduction of Ethion, a frequently used pesticide in tangerine production was carried out by titanium dioxide (TiO2) photocatalysis with different concentrations (5, 10, 20, 40 and 60 mg ml-1) and exposure times (0, 15, 30, 45 and 60 min) under a UV lamp. To evaluate the oxidation potential by TiO2photocatalysis effects, iodine liberation from the reaction was measured. Iodine yield, which increased with increasing concentration and reaction time, was highest at 60 mg ml-1of TiO2and longest at 60-min exposure time. TiO2photocatalysis at the highest concentration was the most effective (60%) at reducing Ethion concentration with the highest rate of degradation occurring within the first 15 min (60%). When treated for alonger exposure time, the reduction of Ethion became insignificant.